The Role of the School Committee in Improving the Quality of Education at Tegalgede Muhammadiyah Elementary School - Khomarudin, Khomarudin; Sumardjoko, Bambang; Narimo, Sabar (Universitas Muhammadiyah Surakarta, 2024)
This study aims to analyze the role of the school committee in improving the quality of education at SD Muhammadiyah Tegalgede, focusing on the challenges and strategies faced. The research method used is qualitative with a case study approach, where data were collected through in-depth interviews, observation, and document studies. The results show that the school committee plays a role as an advisory, supporting, controlling, and mediating body in enhancing educational quality. The committee is actively involved in providing policy recommendations, fundraising, ensuring financial transparency, and facilitating communication between the school, parents, and the community. However, the main challenges include parental protests over high school fees and dissatisfaction with the quality of school services. To address these issues, the school committee reevaluated the school fees, improved financial transparency, and trained teachers and staff to be more responsive to the needs of students and parents. This study concludes that the role of the school committee is crucial in improving educational quality, although further efforts are needed to enhance parental participation and address resource limitations.